2021
DOI: 10.1177/10778012211034201
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Engaging Significant Adults in Youth Sexual and Relationship Violence Prevention Work

Abstract: Relationship and sexual violence (RSV) disproportionately affect youth in immigrant and other marginalized communities yet few prevention initiatives are truly grounded in their experiences. The current study represents a pilot implementation evaluation of youth-led workshops to engage significant adults (parents, grandparents, aunts, adult siblings, community leaders) as RSV prevention partners in diverse communities in a large urban area. The current mixed methods evaluation examined the perceptions of 66 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Parents and family members were frequently mentioned, sometimes as providing invaluable support to participants and other times, acting in ways that were hurtful and victim blaming. Increasingly, the role of parents and significant adults is being recognized as a key component of effective, comprehensive prevention and response to DSV, but further work is needed to determine how to best engage parents in meaningful ways (Banyard et al, 2021). Similarly, there is recognition that other individuals in schools or universities (such as faculty, staff, and co-workers) have a role to play in witnessing and suspecting abuse; yet, there lacks research on the best ways to engage and activate these individuals to serve in pro-social ways (McMahon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Parents and family members were frequently mentioned, sometimes as providing invaluable support to participants and other times, acting in ways that were hurtful and victim blaming. Increasingly, the role of parents and significant adults is being recognized as a key component of effective, comprehensive prevention and response to DSV, but further work is needed to determine how to best engage parents in meaningful ways (Banyard et al, 2021). Similarly, there is recognition that other individuals in schools or universities (such as faculty, staff, and co-workers) have a role to play in witnessing and suspecting abuse; yet, there lacks research on the best ways to engage and activate these individuals to serve in pro-social ways (McMahon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with other social identity research that suggests one's group identification provides a framework for viewing the world and reducing uncertainty when faced with unexpected situations (Choi & Hogg, 2019; Hogg, 2021). Just as parents provided a source of socialization and information for establishing positive norms for healthy relationships for youth (Banyard et al, 2021), student groups and leaders within student organizations may also provide these norms for group members. It is important to note that a relatively weak effect was observed for each significant correlation in this study, so these effects should be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The creation and evaluation of effective bystander intervention trainings for college students are imperative for future research (Banyard et al, 2007), and many researchers have identified the need to target specific groups with bystander messages (Foubert & Cowell, 2004;Foubert & Perry, 2007;Levine & Crowther, 2008;Mabry & Turner, 2015;McMahon & Farmer, 2009;Sundstrom et al, 2018). Through tailoring to the communities and cultures in which they are implemented, researchers can address specific barriers and create more effective trainings (Banyard et al, 2021;Orchowski et al, 2020). This study explored the relationship between college students' group membership and group identification with student subgroups and their perceptions about bystander intervention to prevent sexual assault.…”
Section: Discussionmentioning
confidence: 99%